Workers’ safety during construction : investigating the integration of safety features into design process in Malaysia construction industry / Norhafizah Yusop, Farhan Md Dahlan and Asmalia Che Ahmad - Yusop, Norhafizah; Md Dahlan, Farhan; Che Ahmad, Asmalia (2012)
Previous construction safety studies in Malaysia addressed current activities and conditions at the construction site but did not consider potential factor or sources involved in the design phase. As safety has been part of an integrated into contractors’ core business activities, previous construction safety studies in Malaysia were focusing solely on the role of the contractor rather than adopting the broader view of accident causality that looks at upstream including the design process. Although construction safety has traditionally rested on the main contractor’s shoulders, architects have been identified as parties to the project team who have a significant influence on construction workers’ safety features and can positively influence construction site safety. The reason is because, an architect is a person trained in the planning, design and oversight of the construction of buildings. Professionally, their decisions during design phase affect construction safety. For this reason, this research attempts to identify and determine the current practices of integrating construction workers safety during designing. A survey, as well as semi-structured interviews were used as methods for data collection. Result revealed that there was some practice in the integration of Construction Workers’ Safety Features during Design Process among Malaysian Architects although the implementation was insignificant. However, the practices were done through individual initiative and informal basis.